Water Kefir Grains—Microbial Biomass Source for Carbonaceous Materials Used as Sulfur-Host Cathode in Li-S Batteries - Paez Jerez, Ana Laura (2022)
Nowadays, the use of biomass to produce cathode materials for lithium–sulfur (Li-S) batteries is an excellent alternative due to its numerous advantages. Generally, biomass-derived materials are abundant, and their production processes are environmentally friendly, inexpensive, safe, and easily scalable. Herein, a novel biomass-derived material was used as the cathode material in Li-S batteries. The synthesis of the new carbonaceous materials by simple carbonization and washing of water kefir grains, i.e., a mixed culture of micro-organisms, is reported. The carbonaceous materials were characterized morphologically, texturally and chemically by using scanning electron microscopy, N2 adsorption–desorption, thermogravimetric analysis, X-ray diffraction, and both Raman and X-ray photoelectron spectroscopy. After sulfur infiltration using the melt diffusion method, a high sulfur content of ~70% was achieved. Results demonstrated that the cell fitted with a cathode prepared following a washing step with distilled water after carbonization of the water kefir grains only, i.e., not subjected to any chemical activation, achieved good electrochemical performance at 0.1 C. The cell reached capacity values of 1019 and 500 mAh g−1 sulfur for the first cycle and after 200 cycles, respectively, at a high mass loading of 2.5 mgS cm−2. Finally, a mass loading study was carried out.